Evaluation of the static and dynamic balance in single and dual tasks among active smokers and non-smokers - Yuvraj Rana; Hina Vaish (PAGEPress Publications, 2023)
Chronic smoking may lead to postural imbalance and there is the risk of injuries due to instability. Balance is needed to maintain posture. Literature is scarce regarding static and dynamic balance in smokers. Hence, the study aimed to evaluate the static and dynamic balance in single and dual tasks among active smokers and age-matched non-smokers.100 smokers and 100 non-smokers aged 20-50 years were selected by purposive sampling. Static balance was assessed by a single-leg stance (SLS) test. Dynamic balance was assessed by performing the time up and go (TUG) test, and 10m walk test. All the tests were performed in single and dual tasks in both smokers and age-matched non-smokers. Kolmogorov-Smirnov test was used for assessing normality. Mann-Whitney U test was used to compare the two groups. pvalue ≤ 0.05 was considered significant. There was a significant difference in the SLS test, 10M walk test, and TUG test in single as well as dual tasks. The static and dynamic balance is impaired in chronic smokers in comparison to age-matched non-smokers and seeks further exploration in larger samples.